The effectiveness of maintenance management in government building / Ahmad Khairul Ngazam Mohd Saibani - Mohd Saibani, Ahmad Khairul Ngazam (Faculty of Architecture, Planning and Surveying, 2010)
Maintenance of government offices building has received increased attention recently. Maintenance is essential to make sure that the government building operates well within life time and ensuring the maximum value for the government building. Maintenance without proper plan will lower the function and performance of the building. The maintenance function is equally dataintensive. Work order forms are issued as equipment and fixtures become due for maintenance. Forms must be completed to document that the work was performed, as well as what procedures were performed. And often, manuals or other documentation may be required in order to properly complete either scheduled or emergency maintenance. The purpose of a Maintenance Effectiveness is to determine where the maintenance organization’s strengths are to leverage improvements and identify areas of opportunity to correct. It provides a view of the structure, relationships, processes and people relative to good maintenance practices. Efficiency and effectiveness of maintenance management realizes heavily on total comprehension and the ability to address the competencies or area of expertise involved and the proper calculation, assembly and conduction of each of its process.